Ectopic Pancreatic Islets in Splenopancreatic Ligament: A Case Report - Aich, Rajarshi; Sutradhar, Arpita; Khan, Enam Murshed; Maitra, Sudipta Kumar; Gupta, Shaikat (Annals of Pathology and Laboratory Medicine, 2022)
Heterotopic or ectopic pancreas is pancreatic tissue present at an abnormal location which is not connected to the main pancreas. They are predominantly located in the gastrointestinal tract, with stomach being the most common site. Mostly asymptomatic, they are usually detected incidentally during surgeries for other conditions. Preoperative diagnosis is very difficult and the definitive diagnosis is histopathological examination of the suspected lesion. Surgical resection is curative and it should be done in asymptomatic cases for diagnostic confirmation and prevention of complications. Here, we present a case of ectopic pancreas in a 59-year-old female in the splenopancreatic ligament which was incidentally identified during histopathological examination of specimen excised for serous cystadenoma of pancreas.